Systolic blood pressure response during exercise testing in symptomatic severe aortic stenosis - Kristofer Hedman; Anna Carlén; Eva Nylander; Éva Tamás; Carl Bellander; Henric Nilsson (Open Heart)
Aims Exercise testing remains underused in patients with aortic stenosis (AS), partly due to concerns about an exercise-induced drop in systolic blood pressure (SBP). We aimed to study the SBP response to exercise in patients with severe symptomatic AS prior to surgery and 1 year postoperatively.Methods Patients scheduled for aortic valve replacement due to severe symptomatic AS were enrolled at a single centre in a prospective observational cohort study. Maximal cardiopulmonary exercise testing (CPET) was performed on a cycle ergometer at baseline and 1 year postoperatively, using standard termination criteria. The SBP response was categorised according to the last measurements of SBP during exercise, in relation to workload (the SBP/watt-slope) as ‘normal’ (>0.25 mm Hg/watt), ‘flat’ (0–0.25 mm Hg/watt) or ‘drop’ (<0 mm Hg/watt).Results 45 patients (28 male, 66±9 years, left ventricular ejection fraction 59%±5%, aortic jet velocity 4.6±0.5 m/s) were included, with pairwise comparison available in 31 cases. There were no adverse events. Preoperatively, 4/45 patients were categorised as ‘drop’, 23 as ‘flat’ and 18 as ‘normal’. There was a change in the distribution of categories from preoperative to postoperative measurements (43% ‘normal’ vs 74% ‘normal’, p=0.0046). Maximal SBP and workload-indexed SBP were higher postoperatively than preoperatively (203±26 vs 182±28 mm Hg, p<0.001 and 0.43±0.14 vs 0.29±0.15 mm Hg/watt, p<0.001).Conclusion As a drop in SBP was infrequent (<10%) in patients with severe symptomatic AS and no adverse events occurred, our results indicate that CPET may be performed under careful monitoring in AS patients. Postoperatively, the SBP reaction improved, with no patient having a drop in SBP.Trial registration number NCT02790008.